2021
DOI: 10.1002/uog.24798
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of soluble fms‐like tyrosine kinase‐1 are associated with adverse outcome in pregnant women with COVID‐19

Abstract: Objective In addition to the lungs, the placenta and the endothelium can be affected by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Soluble fms‐like tyrosine kinase‐1 (sFlt‐1) and placental growth factor (PlGF) are markers of endothelial dysfunction and could potentially serve as predictors of severe coronavirus disease 2019 (COVID‐19). We aimed to investigate the association of serum concentrations of sFlt‐1 and PlGF with the severity of COVID‐19 in pregnancy. Methods This was a prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…PlGF values were not significantly different between severe and non-severe pregnant cases of COVID-19 pneumonia. A subsequent publication by the same group has shown that sFlt-1 MoM values are higher in pregnant women with severe COVID-19 and they can be used as a predictor of medical complications, similarly to sFlt-1/ANG-II [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PlGF values were not significantly different between severe and non-severe pregnant cases of COVID-19 pneumonia. A subsequent publication by the same group has shown that sFlt-1 MoM values are higher in pregnant women with severe COVID-19 and they can be used as a predictor of medical complications, similarly to sFlt-1/ANG-II [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Espino-y-Sosa and colleagues have shown that high levels of sFlt-1/ANG-II are associated with adverse outcomes, including severe pneumonia, intensive care unit (ICU) admission, intubation, viral sepsis, and death, among SARS-CoV-2-infected pregnant women [ 18 ]. Subsequently, the same group has identified higher values of sFlt-1 MoM in pregnant women with severe COVID-19 and that these values could be used as a predictor of medical complications, similarly to sFlt-1/ANG-II [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our population, SARS-CoV-2 infection is an independent inflammation factor, added to the pre-existing due to preeclampsia; the significant increases in sFlt-1 concentrations can explain this compared with women with SARS-CoV-2 infection without preeclampsia. Previously, we suggested that interaction between viral spike protein (S) of SARS-CoV-2 and ACE-2 reduces ACE-2 levels in the cell membrane and generates an imbalance of Ang-II/Ang1-7, causing acute hypoxia, which induction and overproduction of sFlt-1, leading to systemic endothelial damage ( 15 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PE and COVID-19 share a vascular–endothelial physiopathological pathway that may aggravate or worsen women's outcomes when both coexist. We hypothesize that this synergic effect is exemplified in sFlt-1 levels among PE and COVID-19 and that there may be an interaction between hypertensive disorders of pregnancy (HDP), COVID-19, and sFlt-1 levels that is reflected in the incidence of adverse maternal outcomes ( 15 ). Therefore, this study aims to evaluate the association between sFlt-1 levels and adverse maternal outcomes among positive SARS-CoV-2 pregnant women controlled by HDP.…”
Section: Introductionmentioning
confidence: 99%
“…Further research is needed into the risk factors associated with adverse outcomes due to COVID-19 in pregnant women 78,79 , such as gestational age at, and severity of, infection. This would enable early identification of those at increased risk, facilitating the development of antenatal surveillance and targeted intervention, and ensure that they are offered COVID-19 vaccination early.…”
Section: Research Implicationsmentioning
confidence: 99%